A retrospective evaluation of nutrition support in relation to clinical outcomes in critically ill patients with an open abdomen. Issue 3 (May 2019) - Yandell, Rosalie; Wang, Susan; Bautz, Peter; Shanks, Alison; O'Connor, Stephanie; Deane, Adam; Lange, Kylie; Chapman, Marianne
Abstract: Background: Optimising nutrition support in critically ill patients with an open abdomen is challenging. Objectives: The aims of this study were to (i) quantify the amount and adequacy of nutrition support administered and (ii) determine any relationships that exist between mode of nutrition support delivery and clinical outcomes in critically ill patients with an open abdomen. Methods: A retrospective review of critically ill patients mechanically ventilated for at least 48 h with an open abdomen in a mixed quaternary referral intensive care unit. Enteral and parenteral nutrition (ml) administered daily to patients was recorded for up to 21 days. Length of stay in the intensive care unit and hospital and duration of mechanical ventilation (days) were reported. Results: Thirty patients were studied [14 male, 68 y (15–90 y), body mass index 25 kg/m 2 (11–51 kg/m 2 ), Acute Physiology and Chronic Health Evaluation II score 20 (7–41), energy goal 1860 kcal/d (1250–2712 kcal/d)]. Patients received 55% (0–117%) of energy goal and 56% (0–105%) protein goal from either enteral or parenteral nutrition. When enteral nutrition was delivered alone or in combination with parenteral nutrition, patients received 48% (0–146%) of their energy and 59% (19–105%) of their protein goal. Patients fed parenteral nutrition, either alone or as supplementary to enteral nutrition (n = 18), received more energy when compared with those who only received enteral nutrition (n = 9) [65 (27–117) vs 49 (15–89) % energy goal, P = 0.025]. Parenteral nutrition was associated with an increased length of stay in hospital [63 (45–156) vs 45 (17–93) d, P = 0.037]. Conclusion: Patients with an open abdomen receive about half of their nutrition requirements when fed exclusively via the enteral route. Providing combination enteral and parenteral nutrition to reach nutritional goals may not result in better clinical outcomes for patients with an open abdomen.